The Effect Of Transformational Leadership Style, and Work Discipline on Employee Performance at PDAM Office in Lamongan - Tri Andjarwati (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This study aims to determine: (1) the effect of transformational leadership style on employee performance at the Central PDAM office in Lamongan, (2) the effect of work discipline on employee performance at the Central PDAM office in Lamongan, (3) the influence of transformational leadership style, and work discipline. on the performance of employees at the PDAM Central office in Lamongan. This research is a survey research with a quantitative approach. The sample used is employees at the PDAM Central office in Lamongan, totaling 55 employees with a saturated sampling technique. In the implementation in the field this research takes primary data by using a questionnaire. The secondary data other than the primary data obtained, obtained from the general section of the Central PDAM office in Lamongan including company profiles and company organizational structure. The analysis technique used is multiple linear regression analysis while the classical assumption test used includes: Multicollinearity Test, Heteroscedasticity Test, and Data Normality Test. The indicators used in this study are valid (because the value of sig